Development of Drying Schedule of Superior and Conventional Teak Wood of Ten Years-old Planted in Blora, Central Java - Tomy Listyanto; Yusuf Setia Darmawan; Rini Pujiarti; Fanny Hidayati; Ganis Lukmandaru; Joko Sulistyo (Jurnal Ilmu Kehutanan)
The aims of this study were to investigate drying defect characteristics, to develop proper drying schedule, and to analyze the relationship between the developed drying schedule and its wood properties. This study used superior and conventional teak wood of ten years-old planted in Blora, Central Java. Sample from different axial positions (bottom and middle part) and different board thicknesses (20 mm and 40 mm) were taken. Drying schedule was developed in accordance to Terazawa method, which dried the sample for 72 h at a temperature of 100 °C. Initial moisture content, crack, collapse, and honeycombing were observed to determine the proper drying schedule. The developed drying schedule then was related to their characteristics, such origin of the seedling, thickness, density, and heartwood percentage. The proper scheduled was also applied in larger sample and evaluated. The results showed that there were five variations of drying schedule for superior and conventional teak wood. Chi square analysis indicated that the board thickness affect significantly on developing drying schedules. Boards with a thickness of 20 mm can be dried with an initial temperature of 70 °C, the wet bulb depression 7°C, and the final temperature of 105°C. Further, boards with a thickness of 40 mm should be dried with a softer drying schedule with an initial temperature of 60°C, wet bulb depression temperature of 4 °C, and the final temperature of 85°C. Application of the selected drying schedule was succeed without any significant defects.